Principles of Pulmonary Protection in Heart Surgery - Gabriel, Edmo Atique.; Salerno, Tomas. (Springer London : Imprint: Springer, 2010)
Over the past fifty years, advanced techniques and strategies have been developed in the field of myocardial protection during heart surgery requiring cardiopulmonary bypass (CPB), but trials focusing on pulmonary protection have been less frequent. Principles of Pulmonary Protection during Heart Surgery is intended as an useful tool to provide strategies for lung protection during CPB. The many renowned contributors have presented their experience on lung perfusion in both experimental and clinical trials, and have detailed numerous new ideas, concepts and future perspectives to the book. It is thus perfect as a reference for a wide range of professionals, including cardiovascular surgeons, pulmonary surgeons and pulmonologists, transplantation physicians, cardiothoracic anesthesiologists, intensive care physicians, radiologists, basic sciences physicians, cardiologists and cardiothoracic fellows, perfusionists, nurses, and researchers.